Competition and integration in the search for a new paradigm for maintaining biodiversity and ecosystem stability - Rasin Alexander S.; Mosolov Alexander A.; Razina Ylyana A. (E3S Web of Conferences, 2023)
Modern researchers in the humanities and natural sciences hold different and sometimes opposite views on the status of natural objects. The anthropocentric point of view prevails, considering man as the center of the universe and the goal of nature, which originates in the traditions of the Renaissance and the Christian Middle Ages about the transcendence of man and domination over nature. In modern versions of anthropocentrism, human needs and interests have an independent value, and people are regarded as exceptional beings with reason and morality. However, anthropocentrism is negatively perceived in many environmental and ethical discussions, as it has led to an ecological crisis, attributing instrumental value to nature. The biocentric approach, which gives moral status to all living beings, is becoming increasingly common in environmental ethics, and it is based on the principle of "reverence for life". With this approach, nature becomes a goal, not just a means, and all living organisms are considered the highest value. The ecocentric approach recognizes the moral status of ecosystems as a whole, denying the privileged status of people and emphasizing the responsibility of people for a responsible and careful attitude to the world around them.